Tuning surface wettability of molybdenum oxide nanorod mesh by low energy ion beam irradiation. (November 2021) - Dhal, Satyanarayan; Das, Pritam; Patro, Arpita; Swain, Madhuchhanda; Hota, Sheela Rani; Sahu, Dojalisa; Chatterjee, Shyamal
Abstract: In this work, we have studied low energy argon ion-induced modification of surface wetting property of molybdenum dioxide nanorod mesh. The nanorods were deposited on a conductive silicon substrate using a spin coating process. The coated thin films were irradiated at two different fluences of 5 × 10 16 and 1 × 10 17 ions cm −2, respectively. With increasing ion doses, the nanorods tend to bend slightly and a kinky structure is observed in a cross-geometry. While the surface of the as-deposited sample is hydrophilic, the irradiated surface alters into hydrophobic. We have analyzed the morphological and structural properties of the surface in detail to realize the initial and altered wetting properties. Furthermore, the dynamical variations in the contact angle on the molybdenum dioxide surfaces are further investigated to understand the interactions between the water droplet, the sample surface, and the atmosphere. We foresee that such altered surfaces can be helpful to fabricate corrosion-resistant devices. Highlights: 5 keV argon ion is bombarded on Molybdenum oxide nanorods. The nanorods got bent and a kinky structure is detected in a cross-geometry after enhancing ion doses. The pristine surface shows hydrophilic behaviour while the irradiated surface revealed as hydrophobic. Such modified surfaces can be utilized for making corrosion-resistant devices.